Efficacy of Curcuma longa extract in an in vivo model of Rhizopus oryzae infection in neutropenic mice (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Mucormycosis, a life-threatening fungal infection caused by Rhizopus oryzae, disproportionately affects immunosuppressed individuals. Current treatments face significant limitations, necessitating alternative approaches. This study investigates the therapeutic potential of ethanolic extracts of Curcuma longa (C. longa), known for its antifungal and immunomodulatory properties, in a neutropenic mouse model of mucormycosis. Mice were infected with R. oryzae and treated with C. longa extracts at 100, 200 and 400 mg/kg doses. Key parameters assessed included survival rates, body weight, hematological profiles (RBC, HGB, PLT), organ weights, fungal burden in kidney and brain tissues, and immunological responses. The 400 mg/kg dose significantly improved survival rates, hematological recovery, and normalized organ weights, with reductions in fungal burden comparable to standard treatment. Mice also exhibited dose-dependent recovery in systemic health. However, incomplete recovery and some mortalities were noted, highlighting the need for further optimization. These findings suggest C. longa extracts possess antifungal, immunomodulatory, and systemic protective effects, offering a promising natural alternative for mucormycosis management in immunosuppressed hosts. Future research should focus on refining dosing strategies and establishing clinical safety and efficacy profiles.